A review of testing procedures based on the empirical characteristic function: Discussion paper - Meintanis, Simos G. (South African Statistical Journal, 2016)
The empirical characteristic function (ECF) has been in use in statistical inference for nearly fifty years now. We provide an overview of testing procedures based on the ECF within certain statistical models. Specifically our emphasis is on recent developments of ECF procedures for goodness-of-fit testing for parametric families of distributions with structured data, and for the two-sample and the k-sample problem.